Success Rate of Pregnancy and Gender Accuracy as The Result of Artificial Insemination by Using Froozen Semen Sexing on Ongole Hybrid Cattle - Susilawati, T (ANIMAL PRODUCTION, 2005)
This research is meant to recognize the difference among pregnancy rate, service per-conseption (S/C) and pregnancy rate of the first Artificial Insemination or conseption rate (CR) and also calf sex accuracy which is born from Ongole hybrid cattle (PO) through Artificial Insemination with froozen semen deposition resulted from different consentration sexing at the position 4 (korpus uteri) and 4+ (bottom end of kornua uteri). The result of this research shows that Artificial Insemination at the position 4 and 4+ with spermatozoa X: pregant 60% (from 10 cattles); CR for each 50%; S/C : 2.00 and 1.83; IB with spermatozoa Y equivalent 80% while S/C 1.42 and 1.25. (Animal Production 7(3): 161-167 (2005) Key Words : Frozen sexing sperm, Service per conception, Calving rate